2007
DOI: 10.1097/fpc.0b013e3280119349
|View full text |Cite
|
Sign up to set email alerts
|

Beta-2-adrenergic receptor polymorphisms in cystic fibrosis

Abstract: Objectives-Cystic fibrosis (CF), an autosomal recessive disease affecting the lung, pancreas, gut, liver, and reproductive tract, is caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene, which encodes a cyclic adenosine 3′, 5′ monophosphateregulated chloride channel. The variability of disease progression among patients with CF suggests effects of genetic modifiers of disease. Beta-2 adrenergic receptors (β 2 AR), which are abundant in airway epithelial cells, accelerate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
(92 reference statements)
0
15
0
Order By: Relevance
“…Published studies have examined mostly immune or inflammatory genes, including ACE [19,20], ADRβ2 [2023], ATB 0 [24], CAPN10 [25], ClCN2 [26], DEFβ4 [27], ENaC [28], FcβRII [29], GCLC [30], GSTM1 [20,31–35], GSTM3 [34], GSTP1 [20,3335], GSTT1 [34], HFE [36,37], HLA-I [38], HLA-II [3841], HLA-III [38], HSP70 [39], IFN-γ [19], IL1-β [39], IL6 [25], IL10 [19,20,42], IL18 [25], KCNJ11 [25], MBL2 [20,4352,53 •• ], MIF [54], NOS1 [5557], NOS3 [20,58], MASP-2 [48,51], PPARβ [25], SERPINA1 [20,59–67], SERPINA3 [68], SFTPA1 [50], SFTPA2 [50], TLR4 [69], TGFB1 [19,20,52,53 ββ ,67,7072 •• ,73 •• ], TNFα [19,20,25,32,52,7476], TNFα -receptor [28], and TNFβ [39]. …”
Section: Candidate Gene Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Published studies have examined mostly immune or inflammatory genes, including ACE [19,20], ADRβ2 [2023], ATB 0 [24], CAPN10 [25], ClCN2 [26], DEFβ4 [27], ENaC [28], FcβRII [29], GCLC [30], GSTM1 [20,31–35], GSTM3 [34], GSTP1 [20,3335], GSTT1 [34], HFE [36,37], HLA-I [38], HLA-II [3841], HLA-III [38], HSP70 [39], IFN-γ [19], IL1-β [39], IL6 [25], IL10 [19,20,42], IL18 [25], KCNJ11 [25], MBL2 [20,4352,53 •• ], MIF [54], NOS1 [5557], NOS3 [20,58], MASP-2 [48,51], PPARβ [25], SERPINA1 [20,59–67], SERPINA3 [68], SFTPA1 [50], SFTPA2 [50], TLR4 [69], TGFB1 [19,20,52,53 ββ ,67,7072 •• ,73 •• ], TNFα [19,20,25,32,52,7476], TNFα -receptor [28], and TNFβ [39]. …”
Section: Candidate Gene Studiesmentioning
confidence: 99%
“…In regard to clinical phenotypes, only effects on lung disease were investigated by more than one study. Three studies [20,22,23] saw no association of lung disease with the codon 16 or codon 27 polymorphisms, although one study [21] reported worse function and decline in individuals who carried a Gly/Gly or Arg/Gly genotype at codon 16 or a Glu/Glu or Gln/Glu genotype at codon 27.…”
Section: Candidate Gene Studiesmentioning
confidence: 99%
“…The effectiveness of asthma’s response to the BD is dependent on polymorphisms in ADRB2 gene . In contrast, with CF, little is known about the response to the BD and the CF´s severity in association with the different polymorphisms in ADRB2 gene [17-19]. Although previous studies had showed an association between bronchodilator response and the polymorphisms in the ADRB2 gene, these studies did not take into account secondary clinical variables that can provide extra information about the mechanism associated with action of the ADRB2 protein.…”
Section: Introductionmentioning
confidence: 99%
“…The c.46AϾG and the c.79CϾG variants have also been associated with hypertension, 21 heart failure 22,23 obesity and metabolic alterations, 24,25 dislipoproteinemia, and type II diabetes, 26 in predicting survival associated with ␤-blocker therapy after acute coronary syndrome 27 and cystic fibrosis. 28 These findings have generated considerable interest in the development of molecular assays to detect ADRB2 allelic variants. These assays have relied on preliminary amplification of ADRB2 sequences by polymerase chain reaction (PCR) and subsequent identification by a variety of methods such as direct sequencing, 29 allele-specific oligonucleotide hybridization, 10,30 and allele-specific multiplex PCR with agarose gel detection.…”
mentioning
confidence: 99%